Children and HIV/AIDS stories, photos and background information from 24 country offices - United Nations Children's Fund (Geneva: UNICEF, 2005)
Its a collection of testimonies that paint a picture, at once colour ful and realistic of the challenges faced in UNICEF's first steps in th e global HIV/AIDS campaign.
Systems requirements: Adobe reader
Keywords: AIDS (Disease) in children